Профетизм модерної німецької філософії: К. Маркс і Е. Гусерль - Пролеєв, С. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
The author explores the quasi religious encroachment of Husserl's phenomenology that is generalized in the notion of «prophetism». Modern philosophy demonstrates the following paradox: though it declares itself to be determined by scientific ideal, anyway, realization of this intention causes quasi religious phenomena and effects. Obviously, the objective truth of thought is attained in order to make possible the domination of prophetic spirit. This is the specific feature of German modern philosophy, specifically of Husserl's. The paper discusses Husserl's' analysis of the «crisis of European humankind» and his idea of the «spiritual Europe» (Vienna Speech, 1935). In order to make evident its specific commitment Husserl's position is compared with Marxist materialistic conception. This is rather helpful in underlining the common logic of these two philosophies. The paper marks out the following elements constituting the prophetic position: primacy of idea over reality; reduction of reality to privileged ontological instance; radical disparagement of any other opinion as untrue; emancipation from untruth by way of soteriological practice; and defining true reality and legitimating one's own philosophy as the way to achieve it. Thus, both Husserl's phenomenology and Marx's materialistic understanding of history turn into the messiah able to rescue the world from the captivity of a deleterious existence. Thus philosophy becomes the propaganda of Weltanschauung.